The cost-effectiveness of mental health interventions amongst prison populations: a systematic review (research letter to the editor) - Rowlandson, Aleix (The journal of forensic psychiatry & psychology, 2024)
The link between imprisonment and adverse mental health is well established and linked to both recidivism and prison misconduct, with negative consequences for prisoners, the prison system and society. To help minimise these impacts, appropriate mental health interventions are required. However, owing to finite resources to deliver healthcare in prisons, interventions must be both clinically and cost-effective. A systematic literature search was conducted using various medical and economic databases. The search aimed to identify full economic evaluations (comparing costs and consequences of two or more interventions) of mental health interventions for adult prisoners during incarceration. Results were intended to identify evidence gaps and highlight areas for future research. Only one publication met all eligibility requirements, with several limitations identified. This finding highlighted a clear lack of cost-effectiveness evidence for use by decision makers within the prison setting. This emphasises the need for future research to incorporate economic evaluation during the early stages of research design. Research should aim to incorporate both intervention costs and wider healthcare resource use, which may be affected, and generic outcomes, such as quality-adjusted life years (QALYs), which enable comparison across various disease areas and against pre-determined thresholds.